Estudo do desempenho de argamassas com resíduo lignocelulósico como substituto parcial do cimento - Dantas, Bruna Ferraz Carvalho (2020)
The construction industry, one of the most important productive and economic activities, is also responsible for environmental impacts like the extraction of raw materials, generation of waste and cement manufacturing, among others. The main objective was to study the technical feasibility of applying the residue generated by the second-generation ethanol obtained from sugarcane to partially replace the cement in concrete mixtures. The residue has lignin in its composition and was applied without further industrial processing. In addition, the research sought to obtain answers regarding the performance of these compositions in relation to the workability in the fresh state and the compressive strength and durability in the hardened state and compared the possible behavior differences between the residues with and without the presence of superplasticizer and plasticizers, both chemical admixtures. The results showed that there was compatibility between the residues and chemical admixtures; the setting time and the consistency index increased with the application of the residues; the compressive strength with residues was lower than the reference composition, but still demonstrated feasibility; in all the tests carried out the durability improved in the residue compositions. Thus, the results were very promising and pointed to major developments.